2022
DOI: 10.3390/pathogens11040468
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tick-Borne Pathogens in Questing Ixodes ricinus and Dermacentor reticulatus Ticks Collected from Recreational Areas in Northeastern Poland with Analysis of Environmental Factors

Abstract: Ticks, such as Ixodes ricinus and Dermacentor reticulatus, act as vectors for multiple pathogens posing a threat to both human and animal health. As the process of urbanization is progressing, those arachnids are being more commonly encountered in urban surroundings. In total, 1112 I. ricinus (n = 842) and D. reticulatus (n = 270) ticks were collected from several sites, including recreational urban parks, located in Augustów and Białystok, Poland. Afterwards, the specimens were examined for the presence of Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
7
7
0
1
Order By: Relevance
“…The infection prevalence determined in our study was comparable to infection rates reported from two other Polish urban agglomerations: the city of Warsaw (1.3%) in central Poland [48] and the city of Olsztyn (3.5%) in north-eastern Poland [49]. In Poland, the highest B. miyamotoi prevalences (6.4-8.4%) were noted in suburban recreational areas of the city of Białystok in northeastern Poland [50]. However, so far, no endemic or risk sites in Poland have been identi ed for B. miyamotoi.…”
Section: Discussionsupporting
confidence: 84%
“…The infection prevalence determined in our study was comparable to infection rates reported from two other Polish urban agglomerations: the city of Warsaw (1.3%) in central Poland [48] and the city of Olsztyn (3.5%) in north-eastern Poland [49]. In Poland, the highest B. miyamotoi prevalences (6.4-8.4%) were noted in suburban recreational areas of the city of Białystok in northeastern Poland [50]. However, so far, no endemic or risk sites in Poland have been identi ed for B. miyamotoi.…”
Section: Discussionsupporting
confidence: 84%
“…Particularly interesting is the detection of B. burgdorferi s.l. in many D. reticulatus ticks, which are not competent vectors of this pathogen, as suggested by some researchers [12,37,38]. Rudolf and Hubalek [39] showed that the salivary gland and midgut extracts in this species inhibited the development of one of the B. burgdorferii s.l.…”
Section: Discussionmentioning
confidence: 84%
“…Podlaskie Province, bordering the north of Lublin Province, is characterised by the highest incidence of tick-borne diseases recorded in Poland, and the prevalence of B. burgdorferi s.l. in this region, on average, is 25.2% in questing I. ricinus ticks and only 0.7% in D. reticulatus [12].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Lenkijos šiaurinėje dalyje ištyrus Ixodes ricinus ir Dermacentor reticulates erkėse esančius sukėlėjus, stebėta vos 1,25 proc. koinfekcijos atvejų [12]. Vokietijos regionuose prie Baltijos jūros pakrantės atlikto tyrimo metu nustatyta, kad po kelis patogenus nešioja maždaug kas ketvirta erkė, tačiau iš 1174 tirtų erkių nebuvo nė vieno EEV ir borelijų koinfekcijos atvejo [13].…”
unclassified